PENERAPAN SISTEM AKUNTANSI SEDERHANA: LAPORAN KEUANGAN UMKM - Hernawati Pramesti, Mujiyono, Indah Handaruwati & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
This study aims to build a Financial Reporting Model Using SimpleAccounting System For SMEs. The approach used is qualitative-phenomenologyapproach to test the implementation of model and analysis is SMEs in Surakarta. Theobservation unit is the owner, member or employee and the facilities andinfrastructure associated with SMEs. The output of this research is one model andsocial engeneering program the form of Financial Reporting Model Using SimpleAccounting System For SMEsKeywords: MSME, Simple accounting system